Flour Mills and Long Distance Routes in South America 16th 17th Centuries); [Molinos Harineros y Rutas de Larga Distancia en América Meridional (Siglos Xvi-Xvii)] - Lacoste, P (Universidad de Tarapaca, 2024)
The role of flour mills and flour in long-distance trade routes in South America is examined. For the Spanish empire, the main focus is on the trans-Pampean route of the Southern Cone of America (Buenos Aires-Mendoza), the Quito-Cuenca-Guayaquil triangle, and the roads of the New Kingdom of Granada, with its connections with Panama and El Callao. For Brazil, the mill on the São Paulo-Santos route is highlighted. It is concluded that the mills contributed to promoting the regional flour trade and, by improving the supply of transporters in ports, inns, and “tambos, ” they consolidated long-distance trade routes and the exchange of typical regional products. © (2024), (Universidad de Tarapaca). All rights reserved.